Typology of Additional Facilities at The Dock of Tambak Lorok Fisherman Settlement in Semarang, Indonesia - Satriya Wahyu Firmandhani (Journal of Architectural Design and Urbanism, 2020)
This study aims to explore the typology of additional facilities at Tambak Lorok dock in Semarang, Indonesia. The revitalized dock is in an appropriate condition with permanent materials and additional facilities that naturally added by user. These facilities are intended as spaces to support fishing activities. This study employed a qualitative paradigm by collecting primary data in the form of interviews with related actors and physical data in the field. The results of this study revealed two categories of additional space properties, namely static and dynamic. The static additional space has a laying pattern at the edge of the dock bordering the settlement or the sea, whereas the dynamic additional space has a laying pattern at the center of the dock